A numerical investigation of static resistance of welded planar steel tubular joints under in-plane and out-of-plane bending at elevated temperatures. (15th November 2019) - Ozyurt, E.; Wang, Y.C.
Highlights: New investigation of elevated temperature tubular joint resistance under in-plane and out-of-plane bending. Modelling of different joint types and tubular shapes with extensive parameters. Developing a simple and accurate design method to calculate elevated temperature resistance. Abstract: This study presents the results of a numerical investigation on static resistance of welded planar steel tubular joints under in-plane and out-of-plane bending moments at elevated temperatures. The numerical simulations were carried out using the commercial finite Element software ABAQUS v6.14-1 and the simulation model was validated by comparing against test results for CHS joints under brace in-plane bending at elevated temperatures. Extensive numerical parametric simulations were performed for CHS/SHS/EHS joints under in-plane and out-of-plane bending at elevated temperatures, to establish a database of results covering a wide range of geometrical parameters, including brace to chord diameter ratio, the angle between brace to chord members, and chord diameter to twice chord thickness ratio. The ratios of joint elevated temperature resistance to ambient temperature resistance were compared to the steel yield strength reduction factor, the steel Young's modulus reduction factor, and the average of the above these reduction factors at different elevated temperatures. Based on the comparisons, it has been found that using the reduction factor for the yield strength of steel to modify the ambient temperature equations will overestimate the resistance of joints at elevated temperatures. As a simplified and safe recommendation, the ambient temperature joint resistance equations can be modified by the average reduction factors for the Young's modulus and yield strength at elevated temperatures. This modification factor can be increased to the yield strength reduction factor when the brace and chord widths/diameters are the same.